Series of Cadmium(II) Coordination Polymers Based on a Versatile Multi-N-Donor Tecton or Mixed Carboxylate Ligands: Synthesis, Structure, and Selectively Sensing Property - Guo, Xing-Zhe (ACS Omega, 2019)
[Image: see text] Five Cd(II) metal–organic frameworks (MOFs), [Cd(HL)(2)] (1), [Cd(HL)(2)(H(2)O)(2)] (2), [Cd(3)(HL)(2)(obda)(2)] (3), [Cd(2)(HL)(2)(ohmbda)(DMA)(H(2)O)] (4), and [Cd(2)(HL)(btc)(H(2)O)(2)]·3H(2)O (5), were prepared by reactions of Cd(NO(3))(2)·4H(2)O with 1-(1H-imidazol-4-yl)-4-(4H-tetrazol-5-yl)benzene (H(2)L) or mixed carboxylate ancillary ligands of 1,2-benzenedicarboxylic acid (H(2)obda), 5-hydroxy-1,3-benzenedicarboxylic acid (H(2)ohmbda), and 1,3,5-benzenetricarboxylic acid (H(3)btc), respectively. Their structures have been characterized by single-crystal X-ray diffraction, elemental analysis, infrared spectroscopy (IR), thermogravimetric analysis, and powder X-ray diffraction. Compounds 1 and 2 are supramolecular isomeric frameworks without consideration of the solvent molecules. Complex 1 exhibits a binodal (3, 5)-connected two-dimensional (2D) layer structure with the point (Schläfli) symbol of (5(2)·6)(5(5)·6(4)·7), while complex 2 shows a 2D + 2D → 3D (three-dimensional) framework. Complex 3 is a (3, 5, 6)-connected tetranodal 3D net with the point (Schläfli) symbol of (4·8(2))(2)(4(5)·6·8(4))(2)(4(5)·6(5))(2)(4(8)·6(6)·8). Compound 4 is a (3, 3, 8)-connected trinodal 3D net with the point (Schläfli) symbol based on a binuclear [Cd(2)N(2)O] subunit, while 5 is a 2-nodal (3, 4)-connected 2D V(2)O(5)-type network based on [Cd(2)N(2)(COO)(2)] SBU. The studies of molecular sensing properties show that the luminescent MOFs can be employed as fluorescent sensors for the detection of Fe(3+) and nitro compounds. Compound 1 and 3 exhibit quenching responses for Fe(3+) in dimethylformamide solution with detection limits of 2.3 × 10(–6) and 8.6 × 10(–7) M, respectively. Meanwhile, compound 5 can sense 4-nitrophenol with a detection limit as low as 5.75 × 10(–7) M.